Tertiary Magmatism in Northwestern Kalimantan: Probability of Volcanic Hazard to The Nuclear Power Plant Site Candidate at Gosong Beach, Bengkayang Regency - Pratiwi, Fadiah; Sukadana, I Gde; Draniswari, Windi Anartha; Ngadenin, Ngadenin; Adimedha, Tyto Baskara; Ciputra, Roni Cahya; Argianto, Ekky Novia Stasia; Aminarthi, Erwina; Supraba, Vertika Dhianda; Sunarko, Sunarko (Geological Agency, 2024)
Gosong Beach in Bengkayang, West Kalimantan, is selected as a potential Nuclear Power Plant (NPP) site candidate. Volcanic and intrusive rocks are found in the radius of 150 km from it. Based on IAEA (International Atomic Energy Agency) standard, the main assessment target is volcanic rock that is younger than 10 Ma. However, there are Tertiary volcanic and intrusive rocks next to and cover a wide area around the NPP site that show volcanic activities over the Tertiary period. Therefore, it is necessary to investigate this group of rocks to understand its characteristics. This study aims to characterize the geochemistry and petrology of the Tertiary volcanic and intrusive rocks found in northwestern Kalimantan. The fieldwork was conducted to observe and to take Serantak volcanic rocks, Bawang dacite, Niut volcanics, and Sintang intrusion samples. The XRF and micro-XRF analyses were conducted to characterize the geochemical aspect, while petrography and AMICS analyses were conducted to characterize the mineralogical aspect. The result shows that Serantak volcanic rocks, Bawang dacite, Niut volcanics, and Sintang intrusion are derived from tholeiitic to calc-alkaline as a product of mantel partial melting in the subduction zone which go through fractional crystallization. The volcanic activity was initiated by the rise of primitive parental magma from partial melting in the shallow-depth subducted crust as indicated by the garnet-free HREE pattern, the enrichment of LILE and LREE, and the depleted HREE. The Tertiary magmatism in northwestern Kalimantan was found in a small activity with a small impact on the NPP candidate site at Gosong Beach, Bangkayang.